3D Tensor Reconstruction in X-Ray Dark-Field Tomography: The First Phantom Result - Hu, Shiyang; Riess, Christian; Hornegger, Joachim; Fischer, Peter; Bayer, Florian; Weber, Thomas; Anton, Gisela; Maier, Andreas (Bildverarbeitung für die Medizin 2015, 2015)

A 3-D Scattering Model for Orientation-dependent X-ray Dark-field Imaging - Hu, Shiyang; Maier, Andreas; Hornegger, Joachim; Bayer, Florian; Weber, Thomas; Anton, Gisela; Riess, Christian (Fully Three-Dimensional Image Reconstruction in Radiology and Nuclear Medicine, 2015)

Analysis Of A Deconvolution-Based Information Retrieval Algorithm In X-Ray Grating-Based Phase-Contrast Imaging - Horn, Florian; Bayer, Florian; Pelzer, Georg; Rieger, Jens; Ritter, André; Weber, Thomas; Zang, Andrea; Michel, Thilo; Anton, Gisela (2014)
Several measurements were carried out using melamine foams as phantoms. We analysed the dependency of the deconvolution-based method with respect to the dark-field image on different parameters such as dose, number of iterations of the iterative deconvolution-algorithm and dark-field signal. A disagreement was found in the reconstructed dark-field values between the FFT method and the iterative method. Usage of the resulting characteristics might be helpful in future applications.
Keywords: X-ray imaging; differential phase-contrast; Talbot-Lau interferometry; grating-interferometry ultra small angle X-ray scattering; deconvolution-based reconstruction; Lucy-Richardson deconvolution

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, J.; Fasching, Peter; Wunderle, M.; Heindl, F.; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, M.; Polifka, Iris; Wachter, David Lukas; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Image fusion in X-ray differential phase-contrast imaging - Haas, Wilhelm; Polyanskaya, Maria; Bayer, Florian; Gödel, Karl Christoph; Hofmann, Hannes; Rieger, Jens; Ritter, André; Weber, Thomas; Wucherer, Lukas; Durst, Jürgen; Michel, Thilo; Anton, Gisela; et al. (Medical Imaging 2012: Image Processing, 2012)
Phase-contrast imaging is a novel modality in the field of medical X-ray imaging. The pioneer method is the grating-based interferometry which has no special requirements to the X-ray source and object size. Furthermore, it provides three different types of information of an investigated object simultaneously - absorption, differential phase-contrast and dark-field images. Differential phase-contrast and dark-field images represent a completely new information which has not yet been investigated and studied in context of medical imaging. In order to introduce phase-contrast imaging as a new modality into medical environment the resulting information about the object has to be correctly interpreted. The three output images reflect different properties of the same object the main challenge is to combine and visualize these data in such a way that it diminish the information explosion and reduce the complexity of its interpretation. This paper presents an intuitive image fusion approach which allows to operate with grating-based phase-contrast images. It combines information of the three different images and provides a single image. The approach is implemented in a fusion framework which is aimed to support physicians in study and analysis. The framework provides the user with an intuitive graphical user interface allowing to control the fusion process. The example given in this work shows the functionality of the proposed method and the great potential of phase-contrast imaging in medical practice. © 2012 SPIE.

Implementation of a Talbot-Lau Interferometer in a Clinical-like C-Arm Setup: A Feasibility Study - Horn, Florian; Leghissa, Martino; Käppler, Sebastian; Pelzer, Georg; Rieger, Jens; Seifert, Maria; Wandner, Johannes; Weber, Thomas; Michel, Thilo; Riess, Christian; Anton, Gisela (Scientific Reports, 2018)

Increasing the darkfield contrast-to-noise ratio using a deconvolution-based information retrieval algorithm in X-ray grating-based phase-contrast imaging - Weber, Thomas; Pelzer, Georg; Bayer, Florian; Horn, Florian; Rieger, Jens; Ritter, André; Zang, Andrea; Durst, Jürgen; Anton, Gisela; Michel, Thilo (Optics Express, 2013)
A novel information retrieval algorithm for X-ray grating-based phase-contrast imaging based on the deconvolution of the object and the reference phase stepping curve (PSC) as proposed by Modregger et al. was investigated in this paper. We applied the method for the first time on data obtained with a polychromatic spectrum and compared the results to those, received by applying the commonly used method, based on a Fourier analysis. We confirmed the expectation, that both methods deliver the same results for the absorption and the differential phase image. For the darkfield image, a mean contrast-to-noise ratio (CNR) increase by a factor of 1.17 using the new method was found. Furthermore, the dose saving potential was estimated for the deconvolution method experimentally. It is found, that for the conventional method a dose which is higher by a factor of 1.66 is needed to obtain a similar CNR value compared to the novel method. A further analysis of the data revealed, that the improvement in CNR and dose efficiency is due to the superior background noise properties of the deconvolution method, but at the cost of comparability between measurements at different applied dose values, as the mean value becomes dependent on the photon statistics used. © 2013 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2013.nat.dphy.PI.LEPDF.increa

Performance analysis of X-Ray phase-contrast interferometers with respect to grating layouts - Haas, Wilhelm; Bartl, Peter; Bayer, Florian; Durst, Jürgen; Grund, T.; Kenntner, J.; Michel, Thilo; Ritter, André; Weber, Thomas; Anton, Gisela; Hornegger, Joachim (2010 IEEE Nuclear Science Symposium, Medical Imaging Conference, NSS/MIC 2010 and 17th International Workshop on Room-Temperature Semiconductor X-ray and Gamma-ray Detectors, RTSD 2010, 2010)
The grating-based phase-contrast imaging approach is highly dependent on the quality of the used gratings. While the fabrication of gratings for the soft X-ray range is more or less well controllable, the fabrication for the hard X-ray range (>30 keV) is more challenging as the gratings must have high aspect ratios and thus fine structures. One of the best fabrication technologies for such gratings is LIGA (Lithography, Electroplating and Molding). However, due to such small structures and high aspect ratio it is unavoidable that the gratings become non-perfect and have deformations. Since the fabrication is complex, expensive and time consuming, a simple way is needed to assess the influence of such deformations on the signal and also a simple way to design and test new grating layouts. This work presents a simulation framework for X-ray phase-contrast imaging which allows to model, simulate and assess the quality of arbitrary grating layouts in an easier, cheaper and faster way. Furthermore, it allows the assessment of the quality of new grating layouts as well as of existing gratings. © 2010 IEEE.

Phase-Sensitive Region-of-Interest Computed Tomography - Felsner, Lina; Berger, Martin; Käppler, Sebastian; Bopp, Johannes; Ludwig, Veronika; Weber, Thomas; Pelzer, Georg; Michel, Thilo; Maier, Andreas; Anton, Gisela; Riess, Christian (21st International Conference on Medical Image Computing and Computer Assisted Intervention, 2018)

Reconstruction of scalar and vectorial components in X-ray dark-field tomography - Bayer, Florian; Hu, Shiyang; Maier, Andreas; Weber, Thomas; Anton, Gisela; Michel, Thilo; Riess, Christian (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Grating-based X-ray dark-field imaging is a novel technique for obtaining image contrast for object structures at size scales below setup resolution. Such an approach appears particularly beneficial for medical imaging and nondestructive testing. It has already been shown that the dark-field signal depends on the direction of observation. However, up to now, algorithms for fully recovering the orientation dependence in a tomographic volume are still unexplored. In this publication, we propose a reconstruction method for grating-based X-ray dark-field tomography, which models the orientation- dependent signal as an additional observable from a standard tomographic scan. In detail, we extend the tomographic volume to a tensorial set of voxel data, containing the local orientation and contributions to dark-field scattering. In our experiments, we present the first results of several test specimens exhibiting a heterogeneous composition in microstructure, which demonstrates the diagnostic potential of the metho
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.PI.LEPDF.recons
Keywords: Anisotropic scattering; Grating interferometer; Microstructure orientation; X-ray phase contrast

Report of improved performance in Talbot-Lau phase-contrast computed tomography - Weber, Thomas; Pelzer, Georg; Rieger, Jens; Ritter, André; Anton, Gisela (Medical Physics, 2015)
Conclusions: The authors' results indicate that the assumptions made in former performance analyses are pessimistic. The break-even point, when phase-contrast CT outperforms attenuation CT, is within reach even with realistic, nonperfect gratings. Further improvements to state-of-the-art clinical CT scanners, like increasing the spatial resolution, could change the balance in favor of phase-contrast computed tomography even more. This could be done by, e.g., quantum-counting pixel detectors with four-fold smaller pixel pitches. (C) 2015 American Association of Physicists in Medicine.
Keywords: x-ray imaging; phase-contrast; computed tomography; performance analysis

Shading Correction for Grating-based Differential Phase Contrast X-ray Imaging - Käppler, Sebastian; Wandner, Johannes; Weber, Thomas; Maier, Andreas; Anton, Gisela; Hornegger, Joachim; Riess, Christian (IEEE Nuclear Science Symposium and Medical Imaging Conference (NSS/MIC), 2014)

Signal decomposition for X-ray dark-field imaging - Käppler, Sebastian; Bayer, Florian; Weber, Thomas; Maier, Andreas; Anton, Gisela; Hornegger, Joachim; Beckmann, Matthias; Fasching, Peter; Hartmann, Arndt; Heindl, Felix; Michel, Thilo; Oezguel, Gueluemser; et al. (MICCAI 2014, 2014)
Grating-based X-ray dark-field imaging is a new imaging modality. It allows the visualization of structures at micrometer scale due to small-angle scattering of the X-ray beam. However, reading darkfield images is challenging as absorption and edge-diffraction effects also contribute to the dark-field signal, without adding diagnostic value. In this paper, we present a novel–and to our knowledge the first–algorithm for isolating small-angle scattering in dark-field images, which greatly improves their interpretability. To this end, our algorithm utilizes the information available from the absorption and differential phase images to identify clinically irrelevant contributions to the dark-field image. Experimental results on phantom and ex-vivo breast data promise a greatly enhanced diagnostic value of dark-field image
EVALuna2:6632